Laser dissection-assisted phloem transcriptomics highlights the metabolic and physiological changes accompanying clubroot disease progression in oilseed rape - Blicharz, Sara; Stefanowicz, Karolina; Truman, William; Basińska-Barczak, Aneta; Singh, Deeksha; Kasprzewska, Anna; de Diego, Nuria; Vrobel, Ondřej; Ćavar Zeljković, Sanja; Tarkowski, Petr; Malinowski, Robert (The Plant journal, 2025)
Plasmodiophora brassicae, a soil-borne biotroph, establishes galls as strong physiological sinks on Brassicaceae plants including Brassica napus and Arabidopsis thaliana. We compare transcriptional profiles of phloem dissected from leaf petioles and hypocotyls of healthy and infected B. napus plants. Our results highlight how pathogenesis accompanies phloem-mediated defence responses whilst exerting a strong influence on carbon-nitrogen (C-N) economy. We observe transcriptional changes indicating decreased aliphatic glucosinolate biosynthesis, fluctuating jasmonic acid responses, altered amino acid (AA) and nitrate transport, carbohydrate metabolism and modified cytokinin responses. Changes observed in phloem-dissected from upper versus lower plant organs point to phloem as a conduit in mediating C-N repartitioning, nutrition-related signalling and cytokinin dynamics over long distances during clubroot disease. To assess changes in physiology, we measured AAs, sugars and cytokinins, in phloem exudates from B. napus plants. Despite the decrease in most AA and sucrose levels, isopentyl-type cytokinins increased within infected plants. Furthermore, we employed Arabidopsis for visualising promoter activities of B. napus AA and N transporter orthologues and tested the impact of disrupted cytokinin transport during P. brassicae-induced gall formation using Atabcg14 mutants. Our physiological and microscopy studies show that the host developmental reaction to P. brassicae relies on cytokinin and is accompanied by intense nitrogen and carbon repartitioning. Overall, our work highlights the systemic aspects of host responses that should be taken into account when studying clubroot disease.
Keywords: laser dissection transcriptomics; listy rostlin; Glucosinolates; aminokyseliny; Plasmodiophorida; transkriptom; Arabidopsis; Nitrogen; uhlík; Phloem; Oxylipins; Transcriptome; oxylipiny; clubroot; Cytokinins; regulace genové exprese u rostlin; glukosinoláty; nemoci rostlin; phloem; cytokininy; Gene Expression Regulation, Plant; Carbon; Plant Leaves; dusík; floém; Cyclopentanes; oilseed rape; Plant Diseases; Brassica napus; cyklopentany; Plasmodiophora brassicae; Amino Acids